The Clinical Role of Cardiovascular Magnetic Resonance Imaging in the Assessment of Cardiac Diastolic Dysfunction - Sabreen Bhuiya; Tanzim Bhuiya; Amgad N. Makaryus (Medical Sciences, 2023)
Echocardiography is the gold standard clinical tool for the evaluation of left ventricular diastolic dysfunction (LVDD) and is used to validate other cardiac imaging modalities in measuring diastolic dysfunction. We examined Cardiac Magnetic Resonance Imaging (CMR) in detecting diastolic dysfunction using the time-volume curve-derived parameters compared to echocardiographic diastolic parameters. We evaluated patients who underwent both CMR and transthoracic echocardiography (TTE) within 2 ± 1 weeks of each other. On echo, Doppler/Tissue Doppler Imaging (TDI) measurements were obtained. On CMR, peak filling rate (PFR), time to PFR (TPFR), 1/3 filling fraction (1/3FF), and 1/3 filling rate (1/3FR) were calculated from the time-volume curve. Using the commonly employed E/A ratio, 44.4% of patients were found to have LVDD. Using septal E/E′ and lateral E/E′, 29.6% and 48.1% of patients had LVDD, respectively. Correlation was found between left atrial (LA) size and E/A ratio (R = −0.36). Using LVDD criteria for CMR, 63% of patients had diastolic dysfunction. CMR predicted LVDD in 66.7% of the cases. CMR-derived diastolic filling parameters provided a relatively easy and promising method for the assessment of LVDD and can predict the presence of LVDD as assessed by traditional Doppler and TDI methods.